2019
DOI: 10.1136/bmjoq-2019-000795
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen years of quality improvement education in healthcare: a utilisation-focused evaluation using concept mapping

Abstract: BackgroundThe need for training in quality improvement for healthcare staff is well acknowledged, but long-term outcomes of such training are hard to evaluate. Behaviour change, improved organisational performance and results are sought for, but these variables are complex, multifactorial and difficult to assess.AimThe purpose of this article is to explore the personal and organisational outcomes identified by participants over 14 years of university-led QI courses for healthcare professionals.MethodInspired b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…One study showed that 12% of the hospital admissions resulted in adverse events, 70% of which were preventable (Soop et al, 2009). As a result of these findings, efforts to improve patient safety, quality and reliability have spread through healthcare organisations (Wachter, 2004;Leape and Berwick, 2005;Bergman et al, 2015;Smith et al, 2019). However, the overall impact of these efforts is hard to see and recently published data declared medical error as the third-leading cause of death in the USA (Daniel and Makary, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that 12% of the hospital admissions resulted in adverse events, 70% of which were preventable (Soop et al, 2009). As a result of these findings, efforts to improve patient safety, quality and reliability have spread through healthcare organisations (Wachter, 2004;Leape and Berwick, 2005;Bergman et al, 2015;Smith et al, 2019). However, the overall impact of these efforts is hard to see and recently published data declared medical error as the third-leading cause of death in the USA (Daniel and Makary, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Personal effects were not included in the original purpose of the study, but since they represent significant results, they are explored at the beginning of this section. Other recent studies have also reported on the personal effects of improvement knowledge education (Smith, Alexandersson, Bergman, Vaughn, & Hellström, 2019). In interviews, the respondents in our study described how the acquired knowledge and experience had changed them as individuals.…”
Section: Discussionmentioning
confidence: 64%
“…The respondents described the development of a culture enabling improvement work as an effect of the master's programme. Other researchers have described organisational capability for improvement as an effect of improvement knowledge education (Smith et al, 2019). Culture describes how groups of people, based on shared assumptions jointly solve problems (Schein, 2010).…”
Section: Meso Levelmentioning
confidence: 99%
“…In fact, training healthcare professionals in improvement science has been shown to foster long-term improvement capability on an individual as well as organisational level. 60 On the right-hand side, patient involvement is argued to support a strengthened patient role, thereby promoting a changed power structure. Investigating QI from such a perspective, the study builds on the literature on buyer–supplier relationships.…”
Section: Literature and Conceptual Frameworkmentioning
confidence: 99%